Особисті права і свободи людини у США та їх захист поліцією - Самотуга, Андрій Валерійович; Самотуга, Андрей Валерьевич; Samotuga, Andrey V. (My University, 2007)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.02 – конституційне право. – Одеська національна юридична академія, Одеса, 2007. Систематизовано сучасні підходи до розуміння конституційних особистих прав і свобод людини, визначено їх структуру, місце в загальній системі прав і свобод та їх гарантії. Досліджено передумови становлення й розвитку особистих прав і свобод людини у США та їх конституційно-правове закріплення. Охарактеризовано особливості їх гарантій. Проаналізовано конституційно-правовий механізм захисту поліцією США конституційних особистих прав і свобод людини. Досліджено історичні й правові аспекти, визначено й систематизовано функції, форми й методи діяльності, з’ясовано особливості відповідальності працівників поліції США за діяльність щодо захисту конституційних особистих прав і свобод людини. Запропоновано зміни до законодавства України та шляхи використання досвіду поліції США в діяльності органів внутрішніх справ України щодо захисту конституційних особистих прав і свобод людини.

Диссертация на соискание ученой степени кандидата юридических наук по специальности 12.00.02 – конституционное право. – Одесская национальная юридическая академия, Одесса, 2007. Систематизированы основные подходы к пониманию конституционных личных прав и свобод человека, определены их структура, место в общей системе прав и свобод и гарантии их защиты. Исследованы предпосылки становления и развития личных прав и свобод человека в США и их конституционно-правовое закрепление. Охарактеризованы особенности их гарантий. Проанализирован конституционно-правовой механизм защиты полицией США конституционных личных прав и свобод человека. Исследованы исторические и правовые аспекты, определены и систематизированы функции, методы и формы деятельности, особенности ответственности сотрудников полиции США за деятельность по защите конституционных личных прав и свобод человека. Предложены изменения в законодательство Украины и пути использования опыта полиции США в деятельности органов внутренних дел Украины по защите конституционных личных прав и свобод человека.

The thesis is for candidate degree of law on speciality 12.00.02 – constitutional law. – The Odessa National Academy of Law, Odessa, 2007. The basic approaches to modern understanding of concept of constitutional personal rights and liberties of the man are systematized. The contents of constitutional personal rights and liberties of the man is expanded: besides the right to life, to respect of human dignity, to freedom and personal inviolability, to inviolability of dwelling and privacy, to freedom of speech and press, it has been added the right to health and healthy environment, to private property, to education as free development of the personality, to ethnic identity and to free use of home language. The structure and the place of constitutional personal rights and liberties of the man in the general system of human rights and liberties, and their guarantees is determined. The attention to ambiguity of understanding of “constitutional personal” and “constitutional civil” rights and liberties of the man in the Ukrainian and American law sciences is paid. It has been stated, that, according to the US law studies, civil rights means privileges to which a man may lawfully request governmental assistance. On the other hand, civil liberties means protections enumerated in the first ten amendments of the US Constitution aimed to protect the man against unreasonable intrusions in state action. External and internal preconditions of becoming and development of personal rights and liberties of the man in the USA and their constitutional-legal embodiment are investigated. It has been concluded that the struggle for the independence of new states had its one of the main ground – to protect and fasten basic natural human rights. Features of constitutional personal rights and liberties guarantees are characterized. Among normative-legal guarantees the leading role is played by the Constitution and the Bill of Rights, then comes constitutions of the states; among institutional-legal guarantees – by the judicial branch of state power. The constitutional-legal mechanism of the US police activity in protection of constitutional personal rights and liberties of the man is analyzed as the police is the most numerical on structure and performs the greatest volume of job to protect these rights and liberties. Historical-legal aspects of the development of the US police through issues of human rights are investigated. The US police legislation consists of: federal Constitution, constitutions of the states, federal and state laws, the US Supreme Court rulings, and local police ordinances. It has been found that there is no special police act on federal and most state level. Functions, methods and forms of the US law enforcement activity to protect constitutional personal rights and liberties of the man are determined and systematized. Among police functions are: patrol-administrative, detective, preventive, and special. The leading place is given to proactive activity through taking a new direction of law enforcement activity – community policing, that focuses on crime and social disorder through the delivery of police services that includes aspects of traditional law enforcement, as well as prevention, problem-solving, community engagement, and partnerships, requiring police and citizens to join together as partners in the course of both identifying and effectively addressing these issues. Among methods of the US police activity to protect constitutional personal rights and liberties of the man the police assistance is determined as the most perspective method. Features of the US police liability to protect constitutional personal rights and liberties of the man that includes disciplinary, civil and criminal liability, and also the control and the accountability of police before the state and a society are analyzed. Changes in the Ukrainian legislation and the ways of use of experience of the US police in the Ukrainian law-enforcement activity to protect constitutional personal rights and liberties of the man are offered.
Самотуга А. В. Особисті права і свободи людини у США та їх захист поліцією : автореф. дис. ... канд. юрид. наук : 12.00.02 / А. В. Самотуга; кер. роботи О. Ф. Фрицький; Нац. ун.-т "Одеська юридична академія". – Одеса, 2007. – 19 с.
Keywords: конституційні особисті права і свободи людини; захист; США; поліція; функції; методи й форми діяльності; відповідальність; конституционные личные права и свободы человека; защита; полиция; функции; методы и формы деятельности; ответственность; constitutional personal rights and liberties of the man; the USA; protection; the police; functions; methods and forms; liability